Using collaboration to foster academic integrity. (3rd May 2016) - Prescott, Lynda
Abstract: For students new to higher education, the task of developing their academic writing skills, and particularly the principles and practices of source-referencing, can be daunting. Although institutions and teachers can and do provide positive guidance on this score, all too often students veer into inadvertent plagiarism through lack of confidence and confusion. This case study identifies opportunities through collaborative work to help students approach referencing with greater clarity and confidence. A project with first-year Arts students engaged in collaborative writing encouraged them to attend to their recording and writing-up of source references using individual 'reading and referencing' logs and then passing on completed references to their group's designated bibliographer. Checks on later, solo, assignments by these students indicated that they were less likely to stray into inadvertent plagiarism, whilst feedback from the students themselves pointed towards improved confidence in their academic writing skills and development of study habits conducive to effective self-monitoring.